10x barcode fastq of Anolis allogus used for Supernova de novo assembly - Shunsuke Kanamori; Luis M. Díaz; Antonio Cádiz; Katsushi Yamaguchi; Shuji Shigenobu; Masakado Kawata (figshare, 2022)
10x barcode fastq of Anolis allogus used for Supernova de novo assembly. Paired-end short read data for Supernova de novo assembly were deposited in the DDBJ Short Read Archive database under BioProject accession number PRJDB13431.
Keywords: Evolutionary Biology